Analisis Audit Sistem Informasi Pelayanan Perpustakaan Menggunakan Framework Cobit 5 - Rahayu Utami; Lala Arika; Sri Dewi Novita (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Libraries as information service providers require information systems that can manage data and information effectively and efficiently. Information system audits are needed to evaluate information system performance and ensure organizational goals are achieved. This research aims to analyze library service information system audits using the COBIT 5 framework, because it focuses on services and service requests. The stages of an ABC library service audit include determining audit objectives, identifying library services using the Framework, capability level analysis, testing controls and evidence at the capability level, verifying results, and compiling audit results reports and recommendations. Audits carried out for library services focus on Process Domains DSS01 and DSS02.